The function of the image of the dog in Plato’s Republic - Montoya, María del Pilar (Logos. Anales del Seminario de Metafísica, 2023)
Among the activities essential to the survival and equilibrium of Callipolis, the city described in the Republic, political and military functions occupy a predominant place. To this extent, their exercise is conditional on the possession of a certain number of physical, moral and intellectual qualities, among which is a proportionate mixture of two opposing character traits: gentleness and aggressiveness. To confirm the coexistence of this curious mixture in an individual, Socrates evokes the image of a pedigree dog, in which the coexistence of these two qualities is expressed in its docility towards its masters and its hostility towards strangers. The image of the dog plays a decisive role in the Republic in that it allows Socrates to demonstrate the naturalness of his project and to justify the radical methods for perfecting the genos assigned to political and military functions. The aim of this article is to analyse the theoretical implications of the use of this image as a model of the political order and the way of life of the guardians of the Republic and the way in which this image intervenes in the construction of a conception of physis which, far from being univocal, varies according to the needs of the Socratic argument.